The Effect Of Giving Olive Oil On Diaper Rash In Toddler In The Work Area Ponre Health Center Year 2024 - Sari, Iramaya; Nabila, Nabila (Hayyan Journal, 2025)
Babies have extensive and complex problems, especially skin problems. All babies have very sensitive skin. The relatively thinner skin conditions in babies cause babies to be more susceptible to infections, irritation and allergies. Skin disorders that often arise in babies include atopic dermatitis, seborrhea, boils, miliariasis (diarrhea), allergies, and inflammation in the form of a skin rash known as diaper rash. The aim of this research is to determine the effect of giving olive oil on diaper rash in toddlers in the Ponre Health Center working area in 2024. This research is a type of quasi-experimental research with a pretest-posttest control group design. Data analysis used univariable and bivariable analysis with the chi-square test. The research results showed that the experimental group showed a decrease in the average score from 2.08 (moderate) to 1.33 (mild) after administering olive oil. Meanwhile, in the control group, the average score only fell slightly from 2.09 to 2.02. Based on the chi-square test in the experimental group, it was found that the value of p=0.001<0.05 and based on the chi-square test in the control group, the value was found to be (p=0.112>0.05), which means that there is an effect of giving olive oil on diaper rash in toddlers. The conclusion of this research is that there is an effect of giving olive oil on diaper rash in toddlers in the work area of ​​the Pontre Community Health Center in 2024